THE EFFECT OF EDUCATIONAL VIDEO ON KNOWLEDGE OF EARPLUG UTILIZATION WEAVING WORKERS AT PT X - Nurul Asmaaul Husna; Reni Wijayanti; Rachmawati Prihantina Fauzi (Journal of Vocational Health Studies, 2026)
Background: The textile production process relies on machinery that generates continuous noise exposure. In the weaving area of PT X, noise levels reach up to 98.4 dBA, making the use of earplugs necessary. However, many workers do not use earplugs due to lack of knowledge about earplugs. This is proven by the results of survey of 10 respondents which stated that 80% of respondents were found to have poor knowledge of earplug utilization. Purpose: The purpose of this study is to examine the impact of educational videos on earplug utilization knowledge in weaving workers of PT X. Method: The design of this study was quasi-experimental, comprising a pretest and posttest control group design. A simple random sampling technique was employed to choose research sample of 82 weaving workers. Wilcoxon and Mann-Whitney test were used to assess the data. Result: Following the posttest, the distribution of educational video on the usage of earplugs significantly enhanced knowledge in the intervention group (p-value 0.001) than the control group (p-value 0.239) as measured by the Wilcoxon test. Conclusion: The provision of educational videos has a significant effect on improving weaving workers’ knowledge of earplug use at PT X.